Maximizing Opioid Restitution Funds via a Networked Care Approach: The Baltimore Comprehensive Overdose Response to End the Epidemic (BCORE) Program - Martha O. Jurczak; Kelly E. Dunn; Sara Whaley; Eric Weintraub (Journal of Addiction Medicine, 2026)
Opioid use disorder and overdose are significant public health crises. Treatments for opioid overdose are highly successful yet also extremely decentralized and difficult for patients who are interested in treatment to navigate. Decentralization also slows progress with scaling treatment access and reducing overdose. This Commentary discusses establishment of the Baltimore Comprehensive Overdose Response to End the Epidemic (BCORE), a novel citywide program funded by opioid restitution funds to integrate disparate programs throughout the city, allowing many individual touchpoints to serve as entry to a network of existing treatment services. Through a commercially available technology platform, treatment opportunities throughout the city can be identified in real-time for any patient who interacts with any one of 11 emergency departments, the Fire Department’s Population Health Team, or a new 24/7 telemedicine line. BCORE aims to reduce barriers to entry for treatment in a low-threshold way by leveraging and networking existing but otherwise independent resources together rather than investing in developing new but competing programs. This is a novel application of opioid restitution funds designed to address decentralization of treatments as a core challenge in a way that is sustainable. Overall, the technical process of networking unrelated services across a city is a complex and highly sought-after process and the BCORE program can serve as a roadmap for other municipalities seeking to streamline care for persons suffering with substance use disorder.